ISSUES OF DEVELOPING MODERN COMPETENCES OF FUTURE TEACHERS ON THE BASIS OF THE “FUTURE TEACHER” MODEL - Yursinboyev Jaxongir Mekhrojiddin ugli (Modern American Journals, 2025)
The article deeply analyzes the modern competencies that should be formed in the process of training future pedagogical personnel and the issues of implementing the “Future Teacher” conceptual model in practice. The level of professional training of teachers in the education system, the possibilities of effective use of innovative approaches, as well as the role of the pedagogical personality in ensuring the personal and social development of students are highlighted. The study, along with the theoretical foundations of the development of competencies, extensively covers their practical mechanisms, advanced methods in pedagogical activity, and methods of using modern educational technologies.
Keywords: Future teacher, professional competencies, concept of